The Influence Of The Quality Of Financial Reports On The Performance Of Public Sector Organizations - Dabella Yunia; Galih Fajar Muttaqin (JAK (Jurnal Akuntansi) Kajian Ilmiah Akuntansi, 2022)
The purpose of this study was to examine the quality of financial reports based on gender effect on the performance of public sector organizations (non-government) and to test accountability on the performance of public sector organizations (non-government), as well as to examine the moderation of the variables of public accountability. The data used in this study is primary data. The data source is a Public Sector Organization registered with the Ministry of Law and Human Rights of the Republic of Indonesia (https://ahu.go.id/). The selection of the Banten region in this research location is because Banten has both medium and large public sector organizations. Most are dominated by public sector organizations whose financial operations must be carried out by accountants and public managers. Statistical analysis in this study uses software Partial Least Square (PLS) version 3. The quality of financial reports prepared by women and men in public sector organizations affects the performance of public sector organizations. Accountability affects the performance of public sector organizations. Accountability can moderate the quality of financial reports on the performance of public sector organizations. The results of the research are used as material to find the best solution or possibility in solving social problems, to analyze social phenomena that occur in society.